Myocardial perfusion in patients with systemic lupus erythematosus and low to intermediate risk for coronary artery disease, assessed with 99mtc mibi myocardial perfusion scintigraphy –case reports - Sandevska, Emilija; Pop Gjorcheva, Daniela; Vavlukis, Marija; Damjanovska Krstic, Ljubinka; Majstorov, Venjamin; Kafedjiska, Irena; Mishevska Perchinkova, Snezhana (My University, 2017)
Objective: Due to early and accelerated atherosclerosis, the patients with systemic lupus erythematosus (SLE), asymptomatic for coronary artery disease (CAD) are in particular risk of acute myocardial infarction (AMI). A diagnostic approach for their risk stratification is needed, followed with appropriate management and treatment. Material and Methods: We present three patents with SLE, from two patients cohorts (younger and older-age group), with SLE history for more than 7 years, with more active phase of disease (SLEDAI score 3-5) and atypical chest pain. With low to intermediate risk for CAD according to traditional risk factors for CAD, but with presence of SLE–related risk factors for atherosclerosis, they underwent 99mTc Myocardial perfusion scintigraphy (MPS) (at rest and stress, as one-day protocol) for evaluation of myocardial perfusion and left ventricular (LV) functional abnormalities. Visual and quantitative analysis of perfusion and functional tomoscintigrams detected the presence of one (in 2 patients) or two vessel’s stress-induced ischemia (in 1 patient), with mild to severe intensity and 10-27% extent of ischemic LV myocardial mass. Regions with the perfusion abnormalities were accompanied with wall motion abnormality during the stress study. The global LV functional parameters were normal in both studies (stress vs rest) with higher transient dilation parameter (TID) in one patient, indicating the presence of more profound perfusion abnormalities. Two patients were referred for angiography which in both cases showed no evidence of significant coronary artery stenosis of the major coronary arteries. Along with their higher levels of serum concentrations of endothelin (ET-1) and C-reactive protein (CRP) the myocardial perfusion abnormalities resemble microvascular functional affection. Conclusion: We emphasize the importance of identification of asymptomatic high CAD risk patients with SLE and CAD evaluation in this patients' cohort in order to prevent premature cardiac death. Determination of the clinical pretest probability for CAD and assessment of myocardial perfusion with non-invasive imaging technique such as 99mTc SPECT MIBI MPS may help in detecting the patients that should be subjected to coronary angiography. Even in the case of microvascular dysfunction, without significant obstruction of coronary vassels, prevention and/or treatment of CAD traditional risk factors and better control of the SLE disease can prevent or postpone the accelerated development of atherosclerosis and the decrease the risk of cardiovascular events.
Keywords: systemic lupus erythematosus; myocardial perfusion; coronary artery disease; myocardial perfusion; scintigraphy